Praktek Ketatanegaraan Di Masa Khalifah Rasyidin - Virgia Annisa Almond (STIKes Ibnu Sina Ajibarang, 2024)
The constitution of the Rashidin Caliphs (Abu Bakr, Umar, Uthman, and Ali) had its own characteristics that were different from the Islamic system of government in later times. This study aims to discuss constitutional practices during the Rashidin Caliph. The method used in this study is Descriptive qualitative method. An understanding of the constitution of the time of the Rashidin Caliph is important to understand the history and development of the Islamic system of government. Their governance offers values of fairness, transparency, and deliberation that are relevant for the development of the current system of government. However, it should be understood that the historical context and socio-political conditions at that time were different from today, so they could not be applied literally.